ENVIRONMENT BASED CHARACTER EDUCATION IN KALIMANTAN LITERATURE: AN OVERVIEW OF LITERATURE ECOFEMINISM - arditiya arditiya (Kantor Bahasa Provinsi Maluku Utara, 2023)
Ecological damage on the island of Kalimantan is a phenomenon that occurs due to excessive exploration of natural resources. The impact is in the form of environmental degradation which causes natural disasters in various places. This phenomenon was responded by writers through their monumental works with the theme of the subordination of society due to the threat of ecological damage on the island of Kalimantan. Bantersi technology (reading, interpretation, and application) will optimize the inner contemplation function of students (students) to be able to participate in preserving nature through literary reception media. As an environment and character-based learning approach, the objects used are literature with an environmental perspective on the island of Kalimantan with its ecological dimensions that are synergized with the role of women as important subjects in every ecological issue that exists in one place. The method used in this research is descriptive with a qualitative approach with a literary ecofeminism perspective. The data sources of this research are poetry, short stories, novels and others that contain elements of environmental education for students. The form of data in this study is a motivational story unit related to the research problem. This study uses library techniques (textual) in data collection activities. The data analysis technique used is descriptive argumentative technique.